Application of laminated and metalized films to prolong the shelf life of dried barberries. (May 2021) - Niazmand, Razieh; Yeganehzad, Samira; Niazmand, Azam
Abstract: Barberry is a nutritional and therapeutic crop mostly dried and consumed in bulk. However, the lack of proper packaging leads to the decline of many of its valuable properties. The aim of this study was to investigate the effect of different packaging films on barberries properties during storage. 150 g of freshly dried barberries were kept for 6 months at 25 °C within different packaging materials: (i) low-density polyethylene (LDPE); two laminated layers film including LDPE and polyethylene terephthalate (PET) with a total thickness of (ii) 45 μm (LDPE/PET-45) and (iii) 60 μm (LDPE/PET-60); (iv) oriented polypropylene (OPP); (v) three laminated layers film of OPP (3OPP); (vi) three laminated layers film including LDPE, metalized PET and PET (LDPE/mPET/PET); and (vii) four laminated layers film including LDPE, PET, aluminum foil and PET (LDPE/PET/Al/PET). After six months, the least change in moisture content, the lowest loss of DPPH scavenging capacity (97.9%), the minimum overall color difference, and the least increase in acidity (39.3%) were related to barberries packaged in the LDPE/PET-45 film. This is while the lowest loss of ascorbic acid (99.8%) and anthocyanin (62.8%) contents and the minimum microbial deterioration were related to the LDPE/PET-60 film. On the other hand, the LDPE/PET/Al/PET film entailed the lowest barberry weight loss (0.67%) and the minimum increase in firmness (40.7%), while the 3OPP film providing the best preservation of phenolic compounds. In conclusion, it seems two laminated layers films composed of LDPE and PET are appropriate for the preservation of dried barberries during storage. Graphical abstract: Image 1 Highlights: Two and multi-layers films were served to extend the shelf-life of dried barberries. PET layer lamination with LDPE were employed to improve water and oxygen barrier properties. Combination of metalized layer with aluminum foil and PET layers were used for packaging of dried barberries. The bioactive compounds of barberries were better preserved in the packages of LDPE/PET. The ascorbic acid, anthocyanin, and phenolic compound content were lost during 6 months storage.